Lightning and convective rain over Indian peninsula and Indo-China peninsula - Siingh, Devendraa; Buchunde, P. S.; Gandhi, H.; Singh, Rajesh; Singh, Shubha; Patil, M. N.; Singh, R. P. (My University, 2015)
The impact of surface temperature, CAPE, convective cloud cover, outgoing long wave radiation and aerosol concentrations on lightning flashes and convective rainfall in the Indian peninsular and Indo-China peninsular regions are compared. Results showed that the observed relationships between lightning, precipitation and considered parameters are very complicated. An attempt is made to tie these observed results with physical considerations. For better understanding of involved processes, regional scale simulations to replicate the observed features are required.
Keywords: Lightning; Convective rain; CAPE; Meteorological parameter; Aerosol optical depth